Masculinities in the framework of the gender perspective and Comprehensive Sex Education (Dissertare, 2021)
This research is located within the general framework provided by Studies on Masculinities, from a bioethical perspective, through Comprehensive Sexual Education, with specific reference to law 26,150, 2006, in Argentina. The proposed objectives are: a) to interpret the meanings of masculinity from the constructions supported by social and cultural stories; b) to investigate the relationship between masculinity/ies, power and gender violence; and c) to reflect on the role that should be assigned to the theme of masculinity, within the framework of Comprehensive Sexual Education (ESI, for its acronym in Spanish). The work methodology is framed in the design of documentary research, with a qualitative and hermeneutical orientation. Among the findings, the various meanings of masculinity based on socio-cultural constructs stand out, as well as the contributions that the approach to the notions of masculinity within the framework of ESI can make from the Human Rights paradigm, recognizing the importance of care and prevention. As a final reflection, it is considered unavoidable to adopt transformations in education and in all transmission of knowledge, in order to contribute to gender equality, assuming masculinity /ies and gender issues from a critical and sensitive view of social changes, under a concept that articulates ESI to public policies, related to inclusion, equality and the rights of children and adolescents.
Keywords: masculinities; Bioethics; Human Rights; Comprehensive Sex Education; gender